PENGAMBANGAN BAHAN AJAR BERBASIS DISCOVERY LEARNING MENGGUNAKAN ANDROID PADA MATERI LIMIT FUNGSI KELAS XI SMAN 1 PADANG - SARI RAHMA ANISA (Departemen Matematika, 2021)
Teaching materials are one of the tools that can support learning in achieving learning objectives, but the teaching materials used in learning are not sufficient for all students and the available teaching materials are not able to support learning optimally. This study aims to develop discovery learning based materials using android. This development research uses the Plomp development model which consists of three stages, namely the preliminary stage of the prototype making stage and the assessment stage. Based on the results of data analysis, it shows that discovery learning based teaching materials using android have met the valid criteria in terms of content and construction, and have met the practical criteria in their application based on student questionnaires. Keywords — Teaching materials, discovery learning, Android